STRATEGI PENGUATAN MANAJEMEN USAHA MIKRO KECIL MENENGAH (UMKM) PADA INDUSTRI PENGOLAHAN MAKANAN RINGAN DI KECAMATAN KAMANG MAGEK KABUPATEN AGAM SUMBAR - Ezizwita Ezizwita; Rita Srihasnita; Maivalinda Maivalinda (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract: UMKM as the backbone of national investment must receive greater and easier attention. One weakness found in many UMKM is that business management is not good and efficient. This research is designed to support management concepts that can be created as a strategy to improve management. UKM process snacks in developing their business. This research uses descriptive method using qualitative aspects of UMKM business management such as HR management, marketing management, financial management and production management, analysis through SWOT analysis (strengths, weaknesses, opportunities and threats), so that it can be used as needed, opportunities and challenges issued by the UMKM. Based on the analysis conducted by SWOT, a strategy that can be carried out by UMKM to support its business is obtained. The results of the study concluded in terms of HR management, UMKM must maintain an adequate workforce with adequate skills, and maintain good relationships with customers. In terms of production management, UMKM must maintain good and hygienic product packaging with attractive designs that pay attention to the smooth production process. In terms of marketing management, UMKM must maintain an affordable product price for all groups. This can be used and improved to increase market segments, and also UMKM must increase and enhance marketing that has been established with outsiders. In terms of financial management, UMKM must conduct financial management and supervision well to deal with company loans and ask for working capital assistance from the government to improve UMKM performance. Keywords: Strategy, Management, UMKM, SWOT analysis